1995
DOI: 10.2307/3579138
|View full text |Cite
|
Sign up to set email alerts
|

Killing and Mutation of Chinese Hamster V79 Cells Exposed to Accelerated Oxygen and Neon Ions

Abstract: Mutation induction by accelerated heavy ions to 6-thioguanine resistance (HPRT system) in Chinese hamster V79 cells was investigated using oxygen and neon ions with energies between 1.9 and 400 MeV/mu, corresponding to LET values between 18 and 754 keV/microns, respectively. Because of technical limitations most experiments could be performed only once. Inactivation and mutation induction cross sections, sigma i and sigma m, were obtained from the slopes of the exponential survival and the linear mutation indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Comparisons of calculation [51] to experiments [43][44][45][46] for HPRT mutation in V79 cells are shown in Fig. 3b.…”
Section: Amorphous Track Models Of Radiation Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons of calculation [51] to experiments [43][44][45][46] for HPRT mutation in V79 cells are shown in Fig. 3b.…”
Section: Amorphous Track Models Of Radiation Actionmentioning
confidence: 99%
“…In Fig. 3a, calculations with the IGK model are compared to data [43][44][45][46] for V79 inactivation. The parameters used for inactivation of V79 cells are shown where m=3, D 0 =1.8 Gy, σ 0 =43 µm 2 , and a 0 =1.1 µm.…”
Section: Amorphous Track Models Of Radiation Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers reported that the maximum RBE values in LET-RBE curves for mutation induction with around 100 -200 keV/µm were higher than these of other biological endpoints such as cell killing, but the RBE values in the high LET regions over 200 keV/µm were lower than cell killing in previous repots (Tsuboi et al, 1992;Chen et al, 1994;Stoll et al, 1995;Suzuki et al, 1996;Schmidt et al, 1998;Kiefer et al, 2001). The present data of this study showed the same tendency when compared to our data for cell killing using the same culture system (Tsuruoka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that high-LET radiation such as heavy ions is more effective than low-LET radiation such as X and gamma rays for various biological effects such as the cell-killing effect, transformation, chromosome aberration and mutation induction (Skarsgard et al, 1967;Yang et al, 1985;Hei et al, 1988;Alpen et al, 1993;Alpen et al, 1994;Suzuki et al, 2000;Kiefer et al, 2001;Tsuruoka et al, 2005;Suzuki et al, 2006). The RBE values of maximum efficiency for mutation induction were higher than other biological endpoints such as cell killing (Tsuboi et al, 1992;Chen et al, 1994;Stoll et al, 1995;Suzuki et al, 1996;Schmidt et al, 1998;Kiefer et al, 2001). Furthermore, high-LET radiations were reported to be more cytotoxic and genotoxic than low-LET radiations (Blakely and Kronenberg, 1998;Cucinotta and Durante, 2006).…”
Section: Introductionmentioning
confidence: 99%